Looking Back: Remarkable Articles Published in the Journal of Bangladesh College of Physicians and Surgeons - Rahim, Muhammad Abdur; Nazneen, Rumana; Saiful, Tasnuva; Afroza, Syeda; Begum, Rowshan Ara (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Journal archives are invaluable resources to the scientific community. The Journal of Bangladesh College of Physicians and Surgeons (JBCPS) is one of the leading biomedical journals in Bangladesh. The objectives of the present review were to have an overview to the all published articles in the JBCPS and to identify remarkable articles for republication of the abstracts on the occasion of golden jubilee celebration of the Bangladesh College of Physicians and Surgeons (BCPS). This retrospective review covered all published articles in the JBCPS since its inaugural issue published in August 1983 to the latest issue published in April 2022. Articles were retrieved from different sources; the BCPS Library, the JBCPS office and Bangladesh Journals On-Line (BanglaJOL). For selection of remarkable articles, systematic review and metaanalysis of randomized controlled clinical trials and original articles were considered and review articles, case reports and others were excluded. Articles were evaluated on three main areas: contribution to the field, methods and clarity of presentation. After initial scrutiny by different contributors, a short list containing 43 articles was prepared. This short list was then reevaluated by each authors individually for identification of 20 remarkable articles and the final selection was made jointly in a meeting among them. Over 40 years, the JBCPS has published 1212 different types of articles including 114 editorials, 565 original research articles, 138 review articles, 316 case reports, 37 images and 42 other types of articles. Twenty remarkable articles were selected from different specialties including anaesthesiology, dentistry, endocrinology, gastroenterology, hepatology, infectious diseases, histopathology, medical education, obstetrics and gynaecology, oncology, ophthalmology, pulmonology, paediatrics, psychiatry, surgery, toxicology and other specialties. In spite of its commendable role in publishing scholarly articles over the previous four decades, the JBCPS is expected to contribute more in the future, both in local and international perspectives. J Bangladesh Coll Phys Surg 2022; 40: 62-73